Life Cycle Analysis on Fossil Energy Ratio of Algal Biodiesel: Effects of Nitrogen Deficiency and Oil Extraction Technology - Hou Jian; Yang Jing; Zhang Peidong (The Scientific World Journal)
Life cycle assessment (LCA) has been widely used to analyze various pathways of biofuel preparation from “cradle to grave.” Effects of nitrogen supply for algae cultivation and technology of algal oil extraction on life cycle fossil energy ratio of biodiesel are assessed in this study. Life cycle fossil energy ratio of Chlorella vulgaris based biodiesel is improved by growing algae under nitrogen-limited conditions, while the life cycle fossil energy ratio of biodiesel production from Phaeodactylum tricornutum grown with nitrogen deprivation decreases. Compared to extraction of oil from dried algae, extraction of lipid from wet algae with subcritical cosolvents achieves a 43.83% improvement in fossil energy ratio of algal biodiesel when oilcake drying is not considered. The outcome for sensitivity analysis indicates that the algal oil conversion rate and energy content of algae are found to have the greatest effects on the LCA results of algal biodiesel production, followed by utilization ratio of algal residue, energy demand for algae drying, capacity of water mixing, and productivity of algae.